PREVALENCE OF MORTON’S NEUROMA IN FEMALES WEARING HIGH HEELS AND FLAT SHOES (The Research of Medical Science Review, 2025)
Background: Neuromas are non-neoplastic nerve tissue proliferations characterized by thickening of the nerve around the nerve tissue, primarily effects the middle-aged women and is commonly found in 3rd and 4th toes. Without treatment, Morton’s neuroma (MN) can lead to worsen symptom and reduced mobility. Objective: The aim of the study was to determine the prevalence of Morton’s neuroma in females wearing high heels and flat shoes. Methodology: The descriptive cross-sectional study lasted for 6 months conducted on sample size of 80 calculated from Raosoft software. Through, non-purposive convenient sampling 20 to 30 years old females wearing high heels and flat shoes from 3 months with positive Mulder sign were included in the study. Females who had undergone previous foot surgeries or suffered from recent trauma, pain in other arears were exclude. Mulder sign, foot health care status questionnaire and numeric pain rating scale was used as data collection tools. Results: The results indicated that 76.3% females had prevalent Morton’s neuroma in which positive Mulder’s sign in 34% females wearing heels and 27% in females with flat shoes. 23.8% females experience mild pain, 45% females had moderate pain, and 31.3% had severe pain. There was association of Morton’s neuroma with type of shoes pvalue-0.05. Conclusion: The study demonstrated that Morton’s neuroma was highly prevalent in females wearing high heels that highly association of Morton’s neuroma with type of shoes. P-value was 0.05